Essential Oil Composition and Antimicrobial Activities of Achillea biserrata M. Bieb. and Achillea salicifolia Besser subsp. salicifolia Collected in Turkey - DILEK AZAZ, AYSE; ARABACI, TURAN; KEMAL SANGUN, MUSTAFA (Asian Journal of Chemistry, 2010)
Aerial parts of Achillea biserrata (collected from Gumushane between Trabzon) and A. salicifolia subsp. salicifolia (collected from Ardahan between Gole) were subjected to hydrodistillation to yield their essential oils and were analyzed by GC and GC-MS. The main components of tested essential oils were camphor (36.80-55.26 %), 1,8-cineol (19.35-22.75 %), camphene (16.41-3.23 %) and artemisia alcohol (14.28-3.17 %), respectively. The antibacterial and antifungal activities of tested essential oils were evaluated against Escherichia coli ATCC 25292, Staphylococcus aureus ATCC 6538, Proteus vulgaris NRRL 123, Pseudomonas aeruginosa ATCC 27853, Enterobacter aerogenes NRRL 3567, Listeria monocystogenes ATCC 7644, Serratia marcescens, Candida albicans, Penicillium expansum, Aspergillus flavus, A. niger and Alternaria brassicola. All tested bacteria and Candida albicans were inhibited by the essential oils. The essential oils showed weak antifungal activity against all microfungi tested. Nevertheless, it is found that P. expansum was not inhibited by any essential oils used in this study. Aspergillus niger was also not inhibited by A. biserrata. Alternaria brassicola was the most sensitive microfungi against all the tested essential oils.